2016
DOI: 10.1038/srep29112
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Localized States in GaAsSb Epilayers Grown by Molecular Beam Epitaxy

Abstract: We report the carrier dynamics in GaAsSb ternary alloy grown by molecular beam epitaxy through comprehensive spectroscopic characterization over a wide temperature range. A detailed analysis of the experimental data reveals a complex carrier relaxation process involving both localized and delocalized states. At low temperature, the localized degree shows linear relationship with the increase of Sb component. The existence of localized states is also confirmed by the temperature dependence of peak position and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 40 publications
(47 reference statements)
6
39
1
Order By: Relevance
“…For this purpose, using a mixed beam, Wei's group reported the carrier dynamics in GaAsSb ternary alloys grown by MBE. The growth conditions and Sb component of the GaAsSb alloy samples were as those shown in Table 1 [22]. The results indicated that the localized states are related to the Sb component of the GaAsSb alloy; however, this component also leads to poor crystal quality in the material, and the applications of GaAsSb alloys are limited owing to the deterioration in quality.…”
Section: Epitaxy Of Gasb Materialsmentioning
confidence: 88%
See 2 more Smart Citations
“…For this purpose, using a mixed beam, Wei's group reported the carrier dynamics in GaAsSb ternary alloys grown by MBE. The growth conditions and Sb component of the GaAsSb alloy samples were as those shown in Table 1 [22]. The results indicated that the localized states are related to the Sb component of the GaAsSb alloy; however, this component also leads to poor crystal quality in the material, and the applications of GaAsSb alloys are limited owing to the deterioration in quality.…”
Section: Epitaxy Of Gasb Materialsmentioning
confidence: 88%
“…However, with the component distribution aggregation effect, the optical properties would exhibit a distinct phenomenon, such as emission related to localized states [22]. Unfortunately, there have only been a few reports on the optical properties of GaAsSb materials [43][44][45][46][47][48][49][50].…”
Section: Gasb Alloy Emission Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…GaAsSb was recognized as the important material for fabrication highperformance optoelectronic devices, such as laser diodes, photo-detectors and transistors [5,17,18]. However, the component fluctuations in ternary alloys could cause the localized states in these materials [1,[19][20][21], resulting in carrier localization effect. The carrier localization effect could greatly affect the optical properties of the semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…The carrier localization effect could greatly affect the optical properties of the semiconductors. The emission efficiency could be influenced by localized carriers in semiconductor materials, such as GaAsSb, InGaN, GaAsN and MgZnO [19,[22][23][24]. In addition, the optoelectronic performance of devices can also be tuned by manipulating localized states [25,26].…”
Section: Introductionmentioning
confidence: 99%